The Impact Of Artificial Intelligence Integration In Human Resource Management On Employee Satisfaction: A Meta-Analytic Review Of Challenges And Opportunities. - Aakanksha, Aakanksha; Bhardwaj, Akash (Journal of Neonatal Surgery, 2025)
The growing adoption of Artificial Intelligence (AI) technologies in organizational practices has transformed human resource management (HRM) functions, raising questions about its effects on employee satisfaction. This meta-analytic synthesis examines the link between AI adoption in HRM and employee satisfaction by combining findings from five peer-reviewed empirical studies released between 2022 and 2025. A random-effects model was used with Jamovi statistical software to capture heterogeneity across study settings. The meta-analysis demonstrated a consistently positive effect of AI deployment on Employee Satisfaction across the studies included in the analysis. While there was high heterogeneity among the findings of the studies, suggesting differences in contexts of adoption and application of AI, publication bias tests did not show any appreciable distortion. Equivalence testing also confirmed that the observed effect was statistically significant. These results indicate that, when incorporated thoughtfully, AI has the ability to drive employee satisfaction through enhanced HR processes, customization, and interaction. The research emphasizes the need for organization-specific AI strategies and makes a call for additional research to examine the role of contextual moderators